The Sage Handbook of Industrial, Work and Organizational Psychology: Organizational Psychology (Handbook of Industrial, Work & Organizational Psychology #2) - Neil Anderson; Deniz S. Ones; Handan Kepir Sinangil; Chockalingam Viswesvaran (UK Sage reference, 2018)
The second volume in the SAGE Handbook of Industrial, Organizational and Work Psychology looks in detail at how teams and individuals function and perform. It covers motivation and organizational socialisation as well as the latest research into diversity and organizational culture in the workplace. There are also sections on social networks and how job loss and the experience of unemployment can affect individuals and wider groups within organizations. Part One: Lenses Part Two: Social and Political Order Part Three: Legacies Part Four: Problems and Problematics
Keywords: Nonfiction; Psychology; Organizational psychology